Calidad de vida y edentulismo en la población del asilo de ancianos San Francisco de Asis de Iquitos, 2021 - Rengifo Rengifo, Mayte Katilay (2022)
Objective: To determine the relationship between quality of life and edentulism in the population of the San Francisco de Asís nursing home in Iquitos, 2021. Method: The type of study is quantitative, cross-sectional research design and level of descriptive research; where the elderly population of the Nursing Home San Francisco de Asís, Iquitos 2021 was evaluated through a questionnaire divided into three parts, in the first with general data of age and sex, second the odontogram and a third corresponding to the GOHAI index which is composed of 12 items of 3 dimensions: physical function, psychosocial function and pain and discomfort. Results: The sample was 38 patients, 42.1% of the sample studied presented total edentulism; 57.9% partial edentulism of which the highest percentage of the sample was male where the average age was 77.37 years. Quality of life was regular in 31,6% of the sample, poor in 68,4% and no patient had a good quality of life. Conclusion: There is no relationship between edentulism and quality of life in elderly patients of the San Francisco de Asís Iquitos Asylum 2021 (p=0,155).